2016
DOI: 10.15694/mep.2016.000033
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy "Peer Teaching" in Medical School: A literature review

Abstract: Medical schools in the twenty first century, have undergone drastic changes in their teaching methodologies worldwide, more specifically in the teaching of anatomy. The main goal of any educational institution is the transfer of knowledge from educator to student in an effective manner. This review attempts to bring together the different teaching methodologies used in medical schools in this new era.Medical institutions have a wide variety of different approaches in teaching anatomy. Tradition dictates that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Finally, the individual differences within students, such as spatial abilities and the daily fluctuations in motivation and cognitive load, will determine the impact such a resource has on learning. Many of these confounding variables are well documented in the literature and should be used in conjunction with the evaluation's findings on learner impact when drawing conclusions (Krause and Coates, ; Burgoon et al, ; Pizzimenti and Axelson, ; Abdel Meguid and Khalil, ; Iqbal, ; Pickering, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the individual differences within students, such as spatial abilities and the daily fluctuations in motivation and cognitive load, will determine the impact such a resource has on learning. Many of these confounding variables are well documented in the literature and should be used in conjunction with the evaluation's findings on learner impact when drawing conclusions (Krause and Coates, ; Burgoon et al, ; Pizzimenti and Axelson, ; Abdel Meguid and Khalil, ; Iqbal, ; Pickering, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cadaver dissection sessions, which are supervised by an academic, provide invaluable opportunities for the students to develop fine motor skills and hands‐on anatomical learning through a stress‐free environment (Krähenbühl et al, 2017). The students have access not only to unembalmed donated cadavers but also to embalmed cadavers and prosections along with the opportunity to practice peer‐ teaching (Iqbal, 2016) and question‐answer sessions in the presence of the academic personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the years, peer teaching has been integrated into a number of medical and allied health courses (Brueckner and MacPherson, ; Youdas et al, ; Iqbal, ; Seenan et al, ) and has been identified as an enriching and effective method for learning (Evans and Cuffe, ; Bene and Bergus, ). Implementation of peer teaching in anatomy using cadaveric specimen has been gaining popularity (Han et al, ; Manyama et al, ).…”
Section: Introductionmentioning
confidence: 99%